Gut commensal Parabacteroides goldsteinii plays a predominant role in the anti-obesity effects of polysaccharides isolated from Hirsutella sinensis - Wu, Tsung-Ru; Lin, Chuan-Sheng; Chang, Chih-Jung; Lin, Tzu-Lung; Martel, Jan; Ko, Yun-Fei; Ojcius, David M; Lu, Chia-Chen; Young, John D; Lai, Hsin-Chih (Gut, 2019)
ObjectiveThe medicinal fungus Ophiocordyceps sinensis and its anamorph Hirsutella sinensis have a long history of use in traditional Chinese medicine for their immunomodulatory properties. Alterations of the gut microbiota have been described in obesity and type 2 diabetes. We examined the possibility that H. sinensis mycelium (HSM) and isolated fractions containing polysaccharides may prevent diet-induced obesity and type 2 diabetes by modulating the composition of the gut microbiota.DesignHigh-fat diet (HFD)-fed mice were treated with HSM or fractions containing polysaccharides of different molecular weights. The effects of HSM and polysaccharides on the gut microbiota were assessed by horizontal faecal microbiota transplantation (FMT), antibiotic treatment and 16S rDNA-based microbiota analysis.ResultsFraction H1 containing high-molecular weight polysaccharides (>300 kDa) considerably reduced body weight gain (∼50% reduction) and metabolic disorders in HFD-fed mice. These effects were associated with increased expression of thermogenesis protein markers in adipose tissues, enhanced gut integrity, reduced intestinal and systemic inflammation and improved insulin sensitivity and lipid metabolism. Gut microbiota analysis revealed that H1 polysaccharides selectively promoted the growth of Parabacteroides goldsteinii, a commensal bacterium whose level was reduced in HFD-fed mice. FMT combined with antibiotic treatment showed that neomycin-sensitive gut bacteria negatively correlated with obesity traits and were required for H1’s anti-obesogenic effects. Notably, oral treatment of HFD-fed mice with live P. goldsteinii reduced obesity and was associated with increased adipose tissue thermogenesis, enhanced intestinal integrity and reduced levels of inflammation and insulin resistance.ConclusionsHSM polysaccharides and the gut bacterium P. goldsteinii represent novel prebiotics and probiotics that may be used to treat obesity and type 2 diabetes.